HUBUNGAN PERSEPSI KINERJA PEMERINTAHAN DENGAN KETERPILIHAN CALON PASANGAN PETAHANA DI PILKADA SALATIGA 2017 - Suwardi Aris Tri Haryanto (RESEARCH FAIR UNISRI, 2018)
The 2017 Major Election of Salatiga concluded that the number of earned votes for currentMajor and Vice-Major Yulianto – Muhammad Haris (Yaris) surpass the earned votes for AgusRudianto – Dance Palit Ishak (Rudal). As the incumbent, Yaris were much favored politically.Strategic incumbent variable is a chance to convince public over their government performance.The level of public satisfaction over the performance of Major Yulianto could be the main modal tobuild personal political variable such as popularity, acceptability and electability.This Research use survey data that conducted by the researcher while the 2017 MajorElection of Salatiga is on process. The survey data then analyzed using determination approachwith the result of the 2017 Major Election of Salatiga that being held on 15 February 2017. Aspectof the method used in this survey are using sample frame of Permanent voters list (DPT). Thetechnique used to get the sample are cuplikan random sampling based on the survey location. Thesurvey conduected over 96 TLS with 768 reponden. This survey has 3,5% margin error withsignificance level of 95%.Yaris perceived to have good governing performance of 77%. This incumbent win theelection with 50,5% earned votes. At the unit level data analysis, 23 kelurahan indicates thedistribution are varies. Although there is a relation between good governing performance and theincumbent to be elected, there are many other variable that affect the result.Key word: local election, Salatiga, incumbent, performance,political personal